Reconstruction of Criminal Law Policy in Handling Corruption Crimes Based on Illicit Enrichment to Realize Just Recovery of State Assets - Asep Guntur Rahayu; Ahmad Redi (Journal Customary Law, 2026)
This study aims to analyze the weaknesses of positive criminal law policies in handling corruption crimes against state asset recovery, examine the lack of illicit enrichment norms in the Indonesian criminal law system, and reconstruct a model of illicit enrichment-based criminal law policy through an integrative approach of prevention and enforcement to realize just state asset recovery. The study employs a normative juridical method with a statutory and conceptual approach. The outcomes indicate that Indonesian positive law is still oriented towards the follow-the-act paradigm, so that it has not optimally pursued the proceeds of crime, while the non-adoption of Article 20 UNCAC into national law has created a lack of norms regarding unexplained wealth as an independent offense. The novelty of this study lies in the reconstruction of an integrative model that connects LHKPN, PPATK, taxation, banking, and beneficial ownership tracing through the stages of clarification, audit, disproportionate wealth analysis, asset recovery mediation, litigation, and confiscation while still guaranteeing due process of law, human rights protection, and ultimum remedium. This model produces a formulation of ius constituendum in the form of an ideal norm of illicit enrichment as the missing link in a more effective and equitable Indonesian asset recovery policy.